Pengaruh Return on Equity dan Current Ratio terhadap Dividend Payout Ratio pada Perusahaan Manufaktur Sektor Basic Materials Terdaftar di BEI Periode 2018-2023 - Mohamad Faizun; Mirza Anindya Pangestika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to explore the impact of financial factors, such as Return On Equity, Current Ratio on Dividend Payout ratio in manufacturing companies in the basic Materials sector listed on the IDX from 2018 to 2023. This study uses a quantitative method. The population and sample in this study are the annual financial statements of manufacturing companies in the basic materials sector in 2018-2023. The sample in this study consists of 54 financial statements taken using a purposive sampling technique. The data analysis used in this study is multiple linear regression analysis using the help of the SPSS 22 application. The results of the study show that partially the Return On Equity (ROE) variable has a significant effect on the Dividend Payout Ratio (DPR). Meanwhile, the Current Ratio (CR) variable has no effect on the Dividend Payout Ratio (DPR). Meanwhile, the Current Ratio (CR) variable has no effect on the Dividend Payout Ratio (DPR). Simultaneously, the Return On Equity (ROE) and Current Ratio (CR) variables affect the Dividend Payout Ratio (DPR) with a determination coefficient value of 21.6%.